P2.131 A Clinico-Aetiological and Ultrasonographic Study of Peyronie's Disease. (13th July 2013) - Kumar, B
Abstract : Bhushan Kumar, Murlidhar, Tarun Narang Background: Peyronie's disease (PD) is caused by progressive fibrotic scarring of the tunica albuginea resulting in curvature or other deformities of the erect penis. PD is a psychologically and physically devastating disorder that manifests in middle-aged men. Although long recognised as an important clinical entity of the male genitalia, the aetiology of this disease is poorly understood. Methods: in this retrospective analysis we studied the epidemiology and clinical presentation of PD cases presenting to the dermatology out patient during Jan2001 - Dec2010. Diagnosis of PD was based on medical and sexual history, physical examination and imaging examinations: ultrasound, and colour Doppler ultrasound. Results: Fifty-six men with PD presented during the period of ten years. Their ages ranged from 23 to 70 years. Most of them presented during the early phase of the disease. Most common presenting complaint was penile curvature in 80.95% followed by pain on erection in 66.66%. History of penile trauma was revealed by 9.52% patients. Hypercholesterolemia (60%), hypertension (33.3%) and asymptomatic hyperuricemia (28.34%) were the most common risk factors.32 patients with PD were studied by ultrasonography. Ultrasonogram was more accurate than clinical assessment in delineating the extent of lesions. In one-third of the patients, sonography demonstrated the plaques to be more extensive than had been detected by clinical examination. Conclusions: PD is a fibrotic wound-healing disorder involving the tunica albuginea of the corpora cavernosa leading to a variety of deformities of the genitalia which are associated with significant sexual dysfunction. The clinical symptoms and signs in our study were, in general, similar to those found in the previous studies. Higher incidence of hypertension and hypercholesterolemia in patients with PD may also be to an extent due to patients being in an older age group. However, it is difficult to explain asymptomatic hyperuricemia.